RETRACTED: Cabbage leaves extract gel for breast engorgement during lactation - Safitri, Rahmah Diani; Wijayanti, Krisdiana; Santoso, Bedjo (Universitas Muhammadiyah Purwokerto, 2022)
RETRACTEDFollowing a rigorous, carefully concerned, and considered review of the article published in Medisains Journal to the article entitled “Cabbage leaves extract gel for breast engorgement during lactation” VOL. 20 NO. 3 (2022) 77-81, DOI: https://doi.org/10.30595/medisains.v20i3.15032.The authors declare that they made a substantial error in entering the data, so the research results could not be presented validly and accurately.The document and its content have been removed from Medisains Journal, and reasonable effort should be made to remove all references to this article.